THE APPLICATION DEVELOPMENT ANALYSIS OF NUTRITIONAL STATUS AND DISEASE IN PREGNANT WOMEN USING DEMPSTERSHAFER METHOD BASED ON WINDOWS MOBILE - Pande Undagi, Gede (Universitas Pendidikan Ganesha, 2013)
Pregnancy is a process of fertilization in order to continue the generationresulting in a growing fetush in a womb of a woman. Many pregnant women having a trouble in getting the information about nutrition status and diseases that is common happen in pregnant women. The health problem of pregnant women usually happen because the lack of knowledge in recognizing early symptoms of disease experienced. That is the main reason the need of aplication to help pregnant woman, one which applies Dempster-Shafer method.Dempster-Shafer is a generalization from Bayesian theory about subjectiveprobability. When Bayesian teory needed probability for every question that come up, Dempster-Shafer theory allowed to determine degree of believe for one question on probability for the question that have connection with other. Dempster-Shafer theory have two main idea. First, get the degree of belief for one question from subjective probability for connected question. Second, combined several degree of beliefs based on the non-independence variable on evidence.The implementation of this research is developing using the waterfall research model and using Visual Basic.net programming language with mssql as a database. Software that designed to have a capability to analyze disease and give the information about nutrition status on pregnant women. This software hopefully will help the pregnant women in keeping away the possibility that can harm the health of pregnant women.